Analysis of coalescence process of methane hydrate in emulsion system. (3rd August 2019) - Song, Rencong; Yang, Fan; Shang, Liyan; Wei, Liwa; Wang, Zhe; Liu, Zhiming; Xu, Jie
Abstract: In oil and gas exploitation and pipeline transportation, hydrate formation poses a significant hidden danger to pipeline safety. Hydrates in the pipelines can coalesce easily on the inner wall surface. Therefore, studying the growth characteristics of hydrates in a multicomponent environment is crucial pipeline anti-blocking technology. Hence, two types of white oil emulsion, S85 + T20 and S85 + SDS, were prepared using sorbitol three oleic acid ester, polyoxyethylene sorbitol monoanhydride, and sodium dodecyl sulfate as dispersants. The mechanism of methane hydrate blockage in emulsion and particle systems at 40% moisture content was analyzed. The hydration reaction induction time and phenomenon characteristics of the two were compared, and the effect of the first 30 min particle size change on the hydration reaction was observed by focused beam reflectance measurement. The experimental results indicate that adding particles to the S85 + SDS emulsion system can shorten the time of hydration reaction dissolved gas significantly, while the hydrophilic particle system will reduce the droplet size at a certain concentration, inhibit the heat transfer and mass transfer between molecules, and prolong the induction of hydrate formation.